EVALUASI PEMBELAJARAN PAI KURIKULUM MERDEKA DI SMA MUHAMMADIYAH 1 SRAGEN - Luqman Hakim; Amrul Fahmi; Akbar Fajar Asmara (EDUCATIONAL JOURNAL : General and Specific Research, 2025)
The purpose of this research is to assess how SMA Muhammadiyah 1 Sragen has used the Independent Curriculum (Kurikulum Merdeka) to teach Islamic Religious Education (PAI). The review is primarily concerned with three key areas: preparation, execution, and results. This research uses a qualitative descriptive technique to show how the Independent Curriculum allows for a lot of leeway in terms of learning design, but it also finds several problems, such students' and teachers' adaption to project-based learning and the availability of resources. The findings reveal that the curriculum enhances student engagement and participation but requires further optimization through teacher capacity building and the provision of adequate learning facilities. The study offers strategic recommendations to address these challenges, aiming to improve the overall effectiveness of Islamic Religious Education under the Independent Curriculum.